Global social indicators and the concept of legitimacy. Issue 4 (3rd January 2018) - Siems, Mathias; Nelken, David
Abstract: Global social indicators have become a core point of interest of scholarship in law and other social sciences. The term 'legitimacy' is occasionally mentioned in this literature but without in-depth discussion. This paper aims to fill this gap by way of exploring the relationship between global social indicators and the concept of legitimacy. The crucial issue of such indicators is that, being drafted in a general fashion and based on a quantitative metric, they can be regarded as somehow 'law-like', thus raising questions about their legitimacy. This paper addresses these issues at both the general level of social theory and the operation of indicators in action.